ATAD2 Upregulation Promotes Tumor Growth and Angiogenesis in Endometrial Cancer and Is Associated with Its Immune Infiltration. (28th November 2022) - Wang, Can; Yin, Yue; Sun, Zhenxing; Wang, Yiru; Li, Fei; Wang, Yan; Zhang, Zexue; Chen, Xiuwei
Abstract : Background . Endometrial cancer is one of the three major gynecologic malignancies, and its incidence continues to rise. ATPase family AAA structural domain-containing protein 2 (ATAD2) is an ATPase protein, which is an independent factor for poor prognosis in endometrial cancer. However, its role in the disease is yet to be determined. Methods . The Tumor IMmune Estimation Resource (TIMER) database was used to assess ATAD2 expression in pan-cancer, and the relevance of ATAD2 expression in Uterine Corpus Endometrial Carcinoma (UCEC) in clinical settings was obtained using Gene Expression Profiling Interactive Analysis (GEPIA) and UALCAN analysis. In addition, the Human Protein Atlas database was used to assess ATAD2 protein expression in UCEC. Furthermore, in vitro molecular biology and in vivo functional experiments were employed to ascertain the effect of ATAD2 expression on tumor angiogenesis and tumor growth. UALCAN was used to screen for ATAD2 coexpressed genes, and Sangerbox was utilized to perform Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses of these coexpressed genes. Finally, the TIMER, Tumor Immune System Interaction and Drug Bank (TISIDB), and GEPIA databases were used to analyze the relationship between ATAD2 and immune infiltration. Results . ATAD2 is highly expressed in a variety of tumors, and in UCEC, it plays the role of a protooncogene. Basic experiments revealed that ATAD2 promotes vascular endothelial growth factor expression in endometrial cancer and affects tumor growth and angiogenesis. In addition, GO and KEGG enrichment analyses showed that ATAD2 -associated genes were chiefly enriched in certain signaling pathways, such as herpes simplex virus 1 infection and that ATAD2 was associated with immune infiltration in UCEC. Conclusion . Our findings suggest that ATAD2 promotes tumor growth and angiogenesis in endometrial cancer. Furthermore, ATAD2 is associated with immune infiltration and is a potential diagnostic and therapeutic target.